Analisis Pengaruh Sosialisasi Pajak, Sanksi Pajak dan Kepatuhan Wajib Pajak terhadap Penerimaan Pajak pada Kantor Pelayanan Pajak Madya Medan - Benny Rojeston Marnaek Nainggolan; Sakaria Jonathan Putra Pinem (COSTING : Journal of Economic, Business and Accounting, 2019)
Tax revenue is the largest revenue in the State Budget (APBN) in the last decade. This study aims to determine the effect of Service Quality, Knowledge of Taxes, Tax Examination, Tax Counseling and Tax Sanctions on Taxpayer Compliance at Medan Middle Tax Office. This study applies certain criteria in determining samples which are often referred to as Saturated Samples. This study obtained a sample of 122 questionnaires, 30 were used for validity test and 92 for classic assumption test using SPSS test equipment. The data analysis used is multiple linear analysis and hypothesis testing. The results of the analysis obtained are Tax Dissemination and Compliance does not affect the Tax Revenue. Tax Sanctions have an influence on Tax Receipts. Keywords: Socialization, Tax Sanctions, Taxpayer Compliance, Tax Revenue